The role of management information systems in measuring organisational performance in the KwaZulu-Natal Department of Art and Culture - Ndlovu, Nokuthula Patricia (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPA)--Stellenbosch University, 2015.